Cost–Benefit Analysis of a Chlamydia trachomatis Vaccine Program in Adolescent Girls in the United States. (7th September 2017) - Ditkowsky, Jared; Rahman, Afsana; Hammerschlag, Margaret R; Kohlhoff, Stephan; Smith-Norowitz, Tamar A
Abstract : Our model estimates that a chlamydia vaccination program in high-burden US populations would avert morbidity but without saving cost to healthcare systems. What Is Known: Screening does not always decrease the burden of Chlamydia trachomatis infection; development of a vaccination program is warranted. Past studies have shown benefits of a vaccination program but used limited methodology and variable ranges. What This Study Adds: This study used a novel methodology and range of variables. Results from the analyses revealed that a C trachomatis vaccine would not be cost-saving to the healthcare system, but it could avert significant chlamydia-associated morbidity and death. Abstract: Background: With >1.4 million cases in the United States reported to the Centers for Disease Control and Prevention in 2012, Chlamydia trachomatis infection is a major public health concern. We examined the impact of a C trachomatis vaccination program using a decision-analysis model to estimate the effects of vaccination on C trachomatis –associated costs and morbidity. Methods: We developed a Markov model considering a cohort of 2158117 US females aged 9 to 26 years. Morbidity, death, and healthcare–associated costs associated with chlamydial infection of mothers and fetuses/neonates were calculated over a 17-year time frame. We developed 2 major comparison arms, namely, a C trachomatis vaccination program and no C trachomatis vaccination program. Base-case efficacy and coverage were set to those of human papillomavirus in the United States with all variables, including efficacy and coverage, ranged in sensitivity analyses. Results: On the basis of a base-case analysis, a vaccination program would cost an estimated $710 million for a cohort of 2158117 women over a 17-year period, an increase of $41 million over having no vaccination program. A vaccination program would prevent 34000 cases of C trachomatis infection and 5976 cases of pelvic inflammatory disease. Conclusions: A C trachomatis vaccination program results in increased cost to the healthcare system but averts significant morbidity and death.